Analysis of Education Management Decision-Making Procedures as a Determining Factor for the Success of Educational Institutions - Atiqoh, Atiqoh; Fauzi, Anis; Gunawan, Agus (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
In the article made by the researcher has the purpose of this study is to determine the implementation of decision-making procedures in the study of education management. This type of research is qualitative, with more emphasis on literature study or literature review approaches produced from Google Scholar, Mendeley and Publish or Parish. The stage in searching some literature using a search engine or maybe easier is indexing any type of document. For example, we use with a query containing Social Network subsentences, of course, the number of subsentences will be generated with a list of documents related to the keywords Procedures, Decision making and education management. In an organizational setting, decision making is the most important part of planning activities. Allowing a decision making has an impact on solving problems or even adding to problems. An educational institution is one part of an organized institutional unit, so there are decision-making activities carried out by a leader of an educational institution as a manager. In its implementation, decision making is very important in realizing strategic steps in carrying out planning and activities to be carried out. Therefore, decision making in the world of education; Especially for leaders of educational institutions must be able to choose the right decision alternatives so that the organizational goals of educational institutions in improving the performance and quality of education can be achieved optimally.